The Politeness Strategies Used in The Movie The Chronicles of Narnia - Mac Aditiawarman; Renita Putri Elba (Fakultas Sastra Universitas Ekasakti, 2018)
This research is a pragmatic study on politeness strategies employed by the characters in The chronicles of Narnia movie in the context of family discourse. This research using Brown and Levinson theory about the types of politeness strategies. The objectives of this research are (1) To identify the types of politeness strategies in the chronicles of Narnia movie (2). To analyze the way politeness strategies utterancesthe chronicles of Narnia movie. (3).To describe the function of the politeness strategies used in the chronicles of Narnia movie.This research used descriptive qualitative approach. The data were in the form of utterances which contain politeness strategies. The data source was The Chronicles of Narnia movie script. The data were collected by note-taking technique then they were classified and analyzed. The trustworthiness was attained by using credibility through two kinds of triangulation: by observers and theories.